Soft micropillar interfaces of distinct biomechanics govern behaviour of periodontal cells - Wörtche, Eva; Schulz, Simon; Spatz, Joachim P.; Ziegler, Nelli; Tomakidi, Pascal; Steinberg, Thorsten (European journal of cell biology, 2010)
A soft micropillar extracellular environment of distinct biomechanics is established by fabricating polydimethylsiloxane (PDMS) interfaces with pillar distances of 5, 7, 9 and 11μm and elasticity moduli of 0.6, 1.0 and 3.5 Mega Pascal. To allow for cell adhesion, the biomimetic concept of pillar head fibronectin (FN) biofunctionalisation is applied. This environmental set-up aims at the analysis of favourable conditions for cell behaviour of three periodontal cell-types, here reflected by the establishment of regular cell morphology and optimal collagen gene expression. Biomechanics of these predefined functionalised model surfaces reveal progressive deterioration of regular cell morphology with increasing pillar distance, independent from pillar elasticity and cell type. Analysis of collagen gene expression demonstrates interdependency to the elasticity and the micropattern of the extracellular environment in all cell types under study. The results suggest that biomechanics of the extracellular environment govern tissue-specific cell behaviour in different periodontal cell types. Moreover, they form the basis for the creation of new biomaterials which address distinct cell functions by specific biomechanical properties.